2017
DOI: 10.1504/ijpm.2017.080911
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain agility in EMS ISO 14001 manufacturing firms: empirical justification of social and environmental performance as an organisational outcome

Abstract: In today's sustainable economic world, the rational thought should be the costs of life cycle, resources or supply chain process. Supply chains need to possess agility to achieve environmental performance (EP) and social performance (SP). However, at present, there is very little knowledge and awareness of how these two concepts interact within a supply chain. This paper therefore, aims to develop a conceptual framework to depict how green supply chain agility (GSCA) strengthens the EP and SP within the supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…We analysed 35 papers in this paper. So, the gap and future study agenda for each paper presented in Tables 15-19 Brusset (2016) The responses were perceptual in nature Examining if agility is able to be elevated diversely due to the economic section Testing the way those operational potencies can be integrated with dynamic ones and connected to competitive advantage A more cross-cultural experimental study with large samples is nominated to establish if the outcomes found for France can be widened to other countries Fernando and Saththasivam (2017) EMS ISO 14,001 manufacturing companies were chosen as a research sample Here, data were gathered via a self-reported survey Future studies should replicate this model in non-EMS-ISO-14001 firms across multiple industries Altay et al (2018) This study tested hypotheses using cross-sectional data In the future, researchers could increase the scope by using a multi-method approach to develop a theoretical model using an in-depth multi-case studies approach followed by empirical validation of the research propositions Researchers should do to extend the studies to understand the effects of interdependency and temporal orientation on differential effects of SCA and SC resilience on performance A longitudinal study is needed Ayoub and Abdallah (2019) Data were collected through a single informant from aimed industries The analysis unit for the investigation demonstrated the manufacturing industry The data were collected from industries of diverse sorts, procedures, sizes and export values and volumes. Albeit, control variables had not been taken into account here…”
Section: Re S E Arch G Aps and Future Re S E Arch Ag Endamentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed 35 papers in this paper. So, the gap and future study agenda for each paper presented in Tables 15-19 Brusset (2016) The responses were perceptual in nature Examining if agility is able to be elevated diversely due to the economic section Testing the way those operational potencies can be integrated with dynamic ones and connected to competitive advantage A more cross-cultural experimental study with large samples is nominated to establish if the outcomes found for France can be widened to other countries Fernando and Saththasivam (2017) EMS ISO 14,001 manufacturing companies were chosen as a research sample Here, data were gathered via a self-reported survey Future studies should replicate this model in non-EMS-ISO-14001 firms across multiple industries Altay et al (2018) This study tested hypotheses using cross-sectional data In the future, researchers could increase the scope by using a multi-method approach to develop a theoretical model using an in-depth multi-case studies approach followed by empirical validation of the research propositions Researchers should do to extend the studies to understand the effects of interdependency and temporal orientation on differential effects of SCA and SC resilience on performance A longitudinal study is needed Ayoub and Abdallah (2019) Data were collected through a single informant from aimed industries The analysis unit for the investigation demonstrated the manufacturing industry The data were collected from industries of diverse sorts, procedures, sizes and export values and volumes. Albeit, control variables had not been taken into account here…”
Section: Re S E Arch G Aps and Future Re S E Arch Ag Endamentioning
confidence: 99%
“…They have shown that external and internal managerial procedures elevate agility. Albeit, SCA has not been elevated when managerial processes relevant to visibility have been utilized Fernando and Saththasivam (2017). developed a perceptual framework to illustrate how GSCA (GSCA) empowers the SP and EP within the SC.…”
mentioning
confidence: 99%
“…Competitiveness could be a topic that has perpetually dedicated an enormous a part of organizations focus to itself particularly among producing companies (Fernando, 2017). The survival of corporations during this turbulent world is directly associated with the flexibility of corporations to reinforce their competitive power, that within the in the meantime, the availability chain agility role (Fernando, 2017;Zutshi et al, 2015;).…”
Section: Introductionmentioning
confidence: 99%
“…Competitiveness could be a topic that has perpetually dedicated an enormous a part of organizations focus to itself particularly among producing companies (Fernando, 2017). The survival of corporations during this turbulent world is directly associated with the flexibility of corporations to reinforce their competitive power, that within the in the meantime, the availability chain agility role (Fernando, 2017;Zutshi et al, 2015;). utilizing Associate in Nursing agile supply chain, whereas facilitating the delivery of products from producer to client, provides production conditions to makers in such how that corporations deal with a minimum price of stopping production or buy in of raw materials (Seyedhoseini et al, 2010;Sukati et al, 2012).Accordingly, it are often argued that its aggressiveness and growing trend have junction rectifier producing corporations to use numerous ways and techniques to with success contend, and also the supply chain is one in every of the paradigms of production that has been notably vital during this regard, however the way to succeed it's perpetually been a difficult issue for corporations (Khan & Pillania, 2008).There is an issue among researchers in determination this downside, and it can't be clearly declared what the foremost vital and appropriate variables area unit to realize an organization's agility (Mandal, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many organisations have implemented environmental sustainability initiatives into their business activities [1,2]. Research over the last few decades has suggested that organisations should also consider the role of their supply chain partners when addressing the environmental impacts of their products and services in order to remain competitive [3][4][5]. However, not all organisations find it easy to address environmental impacts associated with their supply chains.…”
Section: Introductionmentioning
confidence: 99%